ANALISIS KESULITAN MEMBACA PEMAHAMAN PADA KELAS III DI SDN BIBISLUHUR 1 SURAKARTA TAHUN AJARAN 2025/2026 - Bramantyo Susilo; Sri Handayani; Jumanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension is an essential skill that must be mastered by elementary school students to support their learning process. However, several students still experience difficulties in understanding reading texts. This study aims to analyze the difficulties in reading comprehension experienced by third grade students at SDN Bibis Luhur 1 Surakarta in the 2025/2026 academic year, identify students’ reading activities at home, and determine the factors that influence these difficulties. This research used a descriptive qualitative approach with a case study strategy. The subjects of this study were third grade students, the classroom teacher, and students’ parents. Data collection techniques included observation, interviews, documentation, and reading comprehension tests. Data validity was ensured through source triangulation and method triangulation, while data analysis used an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results showed that several students experienced difficulties in understanding reading texts, especially in identifying the main idea, understanding the content of the text, and answering questions related to the reading. These difficulties were influenced by several factors such as low reading interest, lack of reading practice at home, and limited parental support in guiding reading activities. Therefore, collaboration between teachers and parents is needed to improve students’ reading comprehension skills.